Leniency, Collusion, Corruption, and Whistleblowing - Reinaldo Luz; Giancarlo Spagnolo (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2016)
Leniency policies offering immunity to the first cartel member that blows the whistle and self-reports to the antitrust authority have become the main instrument in the fight against price-fixing conspiracies around the world. In public procurement markets, however, bid-rigging schemes are often accompanied by corruption of public officials. In the absence of coordinated forms of leniency (or rewards) for unveiling corruption, a policy offering immunity from antitrust sanctions may not be sufficient to encourage wrongdoers to blow the whistle, as the leniency recipient will then be exposed to the risk of conviction for corruption. This paper assesses the extent of this problem by describing and discussing the antitrust and anti-corruption provisions present in a few selected countries, from both common law and civil law regimes. For each of these countries, we try to evaluate whether the legal system presents any solution to limiting the risk that legal provisions against corruption undermine the effectiveness of leniency programs against bid rigging in public procurement. Legal harmonization, coordination and co-operation on procedural and substantive issues, and inter and intra jurisdictions, seem essential to solve this problem. Given the size of public procurement markets and their propensity for cartelization, specific improvements in legislation appear necessary in all the countries considered. Explicitly introducing leniency policies for corruption, as has been recently done in Brazil and Mexico, is only a first step. The antitrust experience has taught us these policies must be carefully designed and sufficiently generous, they should not be discretional, and they must be consistently implemented to achieve their goals of inducing whistleblowing. Hence, the road ahead appears a long one. To increase the effectiveness of leniency in multiple offense cases, we suggest, besides extending automatic leniency to individual criminal sanctions, the creation of a `one-stop-point' enabling firms and individuals to report different crimes simultaneously and receive leniency for all of them at once if they are entitled to it. As long as individual criminal charges are not covered by a coordinated and non-discretional leniency program, there is little hope that these provision will induce any improvement in the fight against corrupting cartels. A more effective way to fight such cartels may then be offering Qui Tam rewards to non-accomplice whistleblowers, as is already done with apparent success by several law enforcement agencies in the US.
Keywords: K21; K42; 330; Antitrust; Bribery; Cartels; Collusion; Corruption; Competition policy; Immunity; Leniency; Public Procurement; Whistleblowers